Investigation of cellular instabilities and local extinction for two-phase flames under microgravity conditions - Kaya Eyice, Deniz; Halter, Fabien; Yozgatlıgil, Ahmet; Gökalp, İskender; Chauveau, Christian (Comptes Rendus. Mécanique)
The initial mechanism of cellular instabilities on the flame surface was investigated experimentally. Firstly, mono-dispersed ethanol droplets were created via the Wilson cloud principle in a spherical combustion chamber, and aerosol ethanol/air flame propagation was tracked under microgravity conditions. Schlieren images revealed that at the beginning of the cellular structure formation, dark spots formed linking to the signal loss in a density gradient. This phenomenon is assumed to be local extinction and quenching on the flame front due to either liquid droplets’ presence or evaporation. To further investigate the observed phenomenon, stagnation flame experiments were performed for rich propane/air gaseous flames with isolated ethanol droplet injection. The evidence for the local extinction on the flame surface due to droplet passage was found via the Chemiluminescence method. The intrinsic instabilities were found to be triggered by the droplets in cases where the flame cannot recover its initial state.